Seismic Performance and Application of Sandwiched Buckling-Restrained Braces and Dual-Core Self-Centering Braces - Chung-Che Chou; Ping-Ting Chung; Ying-Chuan Chen (Institute for Research and Community Services, Institut Teknologi Bandung, 2014)
This paper first presents cyclic test results and the application of the proposed sandwiched buckling-restrained brace (BRB). The proposed BRB can be easily disassembled in the field. This provides an opportunity for inspection of the core after a large earthquake. The mechanics and cyclic behavior of a novel steel dual-core self-centering brace (SCB) are then proposed and introduced, followed by the testing of a dual-core SCB in order to evaluate its cyclic performance. Both braces achieve an excellent target lateral drift performance of up to 2.5%, thus satisfying the seismic requirement by the AISC Seismic Provisions 2010.